THE ROLE OF ZAKAT ACCOUNTING: NORMATIVE AND CONTEXTUAL APPROACH TO CASE STUDY IN INDONESIA - Endang Kartini Panggiarti; Azis Muslim; Baiq Ismiati (Universitas Tidar, 2022)
The aim of this study is to find out about the role of zakat accounting according to PSAK No. 109 and its implementation in Zakat Management Organizations of regions in Indonesia during the period 2015 - 2020. This research method used a qualitative research approach with case study design, which is a review of various scientific studies on the development of zakat accounting based on PSAK No. 109 in Indonesia. The result obtained is that some Zakat Management Organizations still do not fully implement PSAK No. 109. This is because less understand about the standard and the limitations of existing human resources. The recommendation given is that the manager participates in training on PSAK No. 109 and increases the number of administrators.